(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate, ex vivo, the bond strength to dentin of two endodontic cements, one bioceramic Bio-C Sealer and the other resinous AH Plus, through the Push-Out test. All teeth were instrumented with the Protaper Next system up to the x3 file, and filled with a single cone. Thirty samples of anterior teeth were used, divided into two groups (n=15), the BC group (Bio-C Sealer) and the AH group (AH Plus Jet®) both using the single cone technique. The Push-Out test was performed on the apical, middle and cervical thirds of the samples, conducted using a universal testing machine. The comparison between the two endodontic sealers in the three root thirds was performed using two-way analysis of variance for randomized blocks. For multiple comparisons, the Tukey test was used. In the apical third, the bond strength was significantly higher than that found in the middle third, which, in turn, was statistically higher than in the cervical third. However, it was influenced by the root third, both for the AH Plus Jet® cement and for the Bio-C Sealer. It was concluded that both AH Plus Jet® and Bio-C Sealer cements, with analysis of the bond strength through the Push-Out test, behaved in an equivalent way.